Perceptions of portuguese social work students about the effects of the confinement period from Covid-19 pandemic on the teaching/ learning process - Ferreira, Paula Isabel Marques (2022)
Concerns about the impact of the pandemic on the training of university students, in particular social work students, were the starting point for this research. The objective was to know the perceptions of these students about the effects of the substitution of face-to-face classes by distance classes in their teaching/learning process during the confinement period. To this end, a questionnaire was applied, using the Google Docs platform, to all the students enrolled in the 2019/2020 school year, in the degree course in social work at the Lusófona University. The results revealed students’ concerns about the pandemic and its impacts on learning. Although distance learning has been assessed as having negative effects on their learning process, it has not negatively impacted students’ academic outcomes. The results also draw attention to the importance of rethinking teaching/learning methodologies, with a focus on the development of more participatory strategies capable of motivating, attracting the attention and interest of students for learning. Keywords: perceptions, teaching/learning, distance learning, students, social work, covid-19, Portugal.